2014
DOI: 10.2478/hukin-2014-0090
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Effects of Strength Training Vs. Hydro Aerobics on Functional and Cardiorespiratory Ability in Postmenopausal Women

Abstract: The current study aimed to compare the effects of two exercise programs (Strength Training and Hydro Gymnastics) on the functional and cardiorespiratory abilities of Portuguese postmenopausal women. The study population consisted of 38 volunteers (age: 66.9 ± 6.1 years, body mass: 73.70 ± 10.38 kg, and body height: 1.55 ± 0.10 m). Subjects were randomly divided into two experimental groups and one control group: one group performed 24 weeks of strength training (GST; n = 14), another performed 24 weeks of hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 25 publications
0
10
0
3
Order By: Relevance
“…The hand search of the references of all relevant studies identified one relevant study (Arslan, 2011). After removal of duplicates and exclusion of studies based on predetermined criteria, the final sample included 9 RCTs (Araújo et al, 2015;Arslan, 2011;Jasiński et al, 2015;Kantyka, Herman, Roczniok, & Kuba, 2015;Kin-Isler & Kosar, 2006;Melam et al, 2016;Nagle et al, 2007;Novaes et al, 2014;Park et al, 2003) and 5 uncontrolled clinical trials (Duzova et al, 2018;Hallage et al, 2010;Pilch et al, 2017;Ruiz-Montero, Castillo-Rodriguez, Mikalacki, Nebojsa, & Korovljev, 2014;Said, Lamya, Olfa, & Hamda, 2017), the overview of which is shown in Table 2. The final sample included studies published primarily in Europe, Asia, North and South America.…”
Section: Resultsmentioning
confidence: 99%
“…The hand search of the references of all relevant studies identified one relevant study (Arslan, 2011). After removal of duplicates and exclusion of studies based on predetermined criteria, the final sample included 9 RCTs (Araújo et al, 2015;Arslan, 2011;Jasiński et al, 2015;Kantyka, Herman, Roczniok, & Kuba, 2015;Kin-Isler & Kosar, 2006;Melam et al, 2016;Nagle et al, 2007;Novaes et al, 2014;Park et al, 2003) and 5 uncontrolled clinical trials (Duzova et al, 2018;Hallage et al, 2010;Pilch et al, 2017;Ruiz-Montero, Castillo-Rodriguez, Mikalacki, Nebojsa, & Korovljev, 2014;Said, Lamya, Olfa, & Hamda, 2017), the overview of which is shown in Table 2. The final sample included studies published primarily in Europe, Asia, North and South America.…”
Section: Resultsmentioning
confidence: 99%
“…Para o nosso entendimento esta foi a primeira metanálise avaliando a literatura a respeito da capacidade cardiorrespiratória de idosos após um treinamento no meio aquático. Sete estudos foram incluídos nesta revisão e todos verificaram melhoras significativas após o treinamento de hidroginástica ou de corrida em piscina funda no VO 2máx 1,11,12,[16][17][18][19] . O resultado da metanálise apontou para uma melhora significativa nos testes de VO 2max , indicando que o exercício no meio aquático pode ser uma opção eficiente para a melhoria da capacidade cardiorrespiratória.…”
Section: Discussionunclassified
“…Dos sete artigos incluídos a hidroginástica foi o exercício investigado em cinco estudos 11,12,16,18,19 e a corrida em piscina funda foi investigada em dois estudos 1,17 .…”
Section: Descrição Dos Estudosunclassified
“…Inúmeros são os benefícios que a prática regular de exercícios físicos pode proporcionar, como prevenir ou minimizar os declínios gerados pelo envelhecimento, melhora dos movimentos peristálticos resultando em melhora no funcionamento intestinal, trazendo benefícios à saúde do idoso (SILVA et al, 2018). Podendo proporcionar ainda, melhora da composição corporal, das taxas de lipídios no sangue, da força muscular, aptidão cardiorrespiratória, agilidade e flexibilidade garantindo autonomia ao indivíduo (NOVAES et al, 2014).…”
Section: )unclassified